2019
DOI: 10.1097/pq9.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Time: Implementing Appointment-based Family-centered Rounds

Abstract: Background: Family-centered rounds (FCRs) provide many benefits over traditional rounds, including higher patient satisfaction, and shared mental models among staff. These benefits can only be achieved when key members of the care team are present and engaged. We aimed to improve patient engagement and satisfaction with our existing bedside rounds by designing a new FCR process. Methods: We conducted a needs assessment and formed a multidisciplinary FCR committee that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Monash et al (2017) found that despite their model shortening rounds on average by 8 minutes overall, trainees were less satisfied and perceived them to last longer than the previous rounding model. Bekmezian et al (2019) described adding 5-to 10-minute- 69 (87.3%) 5 (6.3%) 5 (6.3%)…”
Section: Outcomes Of Rounds Participation Among Learnersmentioning
confidence: 99%
“…Monash et al (2017) found that despite their model shortening rounds on average by 8 minutes overall, trainees were less satisfied and perceived them to last longer than the previous rounding model. Bekmezian et al (2019) described adding 5-to 10-minute- 69 (87.3%) 5 (6.3%) 5 (6.3%)…”
Section: Outcomes Of Rounds Participation Among Learnersmentioning
confidence: 99%
“…Scheduled rounds are associated with increased participation by the clinical care team and families and should be considered. 61,67 Telehealth use can enable nurse and family participation and access to interpreters. 48,66,81 This has been particularly helpful, given the restrictions necessary in response to the novel coronavirus disease 2019 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The use of FCRs has been associated with a statistically significant increase in the duration of rounding, by an average of 1.0-1.5 minutes, 39,67 which in aggregate may meaningfully impact daily routines for clinicians and nurses, although study results vary. 1,52,61 However, at least 1 research team suggested that a well-executed FCR that produces a clear understanding of the daily care plan may reduce communications later in the day. 67 The duration of FCRs remains difficult to compare across studies, given the variation in the FCR interventions deployed.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations